Vietnam - Country Procurement Assessment Report : Transforming Public Procurement - World Bank (Washington, DC, 2013)
The transition from a centrally planned economy to a "socialist oriented market economy" in Vietnam has called for comprehensive changes in the legal framework of the State. The last ten years have witnessed great progress in the development of the Vietnamese legal system, both in substantive and procedural matters. A number of important legal instruments have been promulgated, such as the Constitution in 1992; the Land Law in 1993; and the Civil Code in 1996. More recent normative instruments include the Commercial Law of 1997 and various Ordinances and Regulations on matters such as foreign investment, management of investment and construction, national bidding procedures, conduct of public employees, control of corruption and thrift in the use of public funds. Procurement in the public sector in Vietnam was governed mainly by Decrees issued by the Government. The key existing legal instruments governing public procurement are summarized in Table 1. In addition, there are other Decrees and Inter-Ministerial circulars, which contain provisions concerning public procurement and use of public funds. The report discusses key issues such as the legal and regulatory framework; procurement procedures and practices; institutional framework; human resources and procurement capacity; state-owned enterprises and gives recommendations. Annexes include: (a) A Review of the 5th Draft of Vietnam Public Procurement Ordinance; (b) A: Legal Framework; (c) Trade Practices; (d) Financial Framework; (e) Public Sector Procurement of Goods/Works; (f) Public Sector Selection of Consultants; (g) Procurement Performance ; (h) Private Sector Procurement; (ix) Checklist Comparing NCB Procedures and World Bank Policy; (i) Classification of Investment Projects; (j) : Available Methods for the Selection of Bidders (k) Construction Industry Reform - Summary Report; (l) Summary of Pertinent Laws and regulations; and (m) NCB Acceptability - Proposed Provisions for Bank legal agreements.